Análise de interação em um jogo educacional de simulação com óculos de realidade virtual de baixo custo - Fonseca, Layon Martins (2019)
Virtual Reality (VR) is becoming more and more popular, growing mainly in the educational area being applied in many types of systems, such as games, simulators, etc. Low-cost devices are helping in this advent of VR, especially head-mounted displays - HMD. Several studies point out that students who use VR education systems improve their performance, are more interested and learn more. VR in computing is a technology that allows the user to “be” in other places without having to leave their current location. Two important features of this technology are immersion and interaction. The more immersive, the more the user has the feeling of being within the virtual environment, which contributes with better attention and concentration. With the new VR devices emergence, many interaction techniques can be combined. This work aims to investigate whether different forms of interaction with conventional keyboard and mouse, only HMD and HMD with joystick can improve immersion, usability and comfort in an educational 3D simulation game with adapted 2D menus. To carry out this study the following procedures and scientific methods were utilised: (i) state-of-the-art on VR in order to identify which inexpensive devices are available and which interaction techniques can be exploited in these resources; (ii) a systematic mapping on the use of VR applied to education; (iii) the design of the experiment, hypothesis definition, structure and pilot test; (iv) the statistical analysis of the data collected and the answer to the research question. The game chosen for the experiment was initially developed for the desktop platform and was implemented two more HMD's versions: (i) one using only the HMD gaze input interaction technique; (ii) another using the HMD with joystick to perform the interaction. The experiment was conducted with 57 high school students divided into three groups. To measure the proposed variables was used: (i) eGameFlow for immersion (FU; SU; YU, 2008); (ii) the System Usability Scale - SUS for usability (BROOKE et al.,1996); (iii) Simulator Sickness Questionnaire - SSQ for comfort (KENNEDY et al., 1993). Finally, the preparation, the cleaning, the coding, the organization, the normality test and the statistical analysis of the collected data are presented. The results show that HMD game versions improved immersion when compared to the desktop version, but did not improve usability. The desktop version was the one that got the best comfort.